Identification of Cbp1, a c-di-GMP Binding Chemoreceptor in Azorhizobium caulinodans ORS571 Involved in Chemotaxis and Nodulation of the Host Plant - Sun, Yu; Xie, Zhihong; Sui, Fu; Liu, Xiaolin; Cheng, Wuzeng (Frontiers in Microbiology, 2019)
Cbp1, a chemoreceptor containing a PilZ domain was identified in A. caulinodans ORS571, a nitrogen-fixing free-living soil bacterium that induces nodule formation on both the roots and stems of the host legume Sesbania rostrata. Chemoreceptors are responsible for sensing signals in the chemotaxis pathway, which guides motile bacteria to beneficial niches and plays an important role in the establishment of rhizobia-legume symbiosis. PilZ domain proteins are known to bind the second messenger c-di-GMP, an important regulator of motility, biofilm formation and virulence. Cbp1 was shown to bind c-di-GMP through the conserved RxxxR motif of its PilZ domain. A mutant strain carrying a cbp1 deletion was impaired in chemotaxis, a feature that could be restored by genetic complementation. Compared with the wild type strain, the ∆cbp1 mutant displayed enhanced aggregation and biofilm formation. The ∆cbp1 mutant induced functional nodules when inoculated individually. However, the ∆cbp1 mutant was less competitive than the wild type in competitive root colonization and nodulation. These data are in agreement with the hypothesis that the c-di-GMP binding chemoreceptor Cbp1 in A. caulinodans is involved in chemotaxis and nodulation.